Detection of Two Highly Diverse Peribunyaviruses in Mosquitoes from Palenque, Mexico - Kopp, Anne; Hübner, Alexandra; Zirkel, Florian; Hobelsberger, Daniel; Estrada, Alejandro; Jordan, Ingo; Gillespie, Thomas R.; Drosten, Christian; Junglen, Sandra (Viruses, 2019)
The Peribunyaviridae family contains the genera Orthobunyavirus, Herbevirus, Pacuvirus, and Shangavirus. Orthobunyaviruses and pacuviruses are mainly transmitted by blood-feeding insects and infect a variety of vertebrates whereas herbeviruses and shangaviruses have a host range restricted to insects. Here, we tested mosquitoes from a tropical rainforest in Mexico for infections with peribunyaviruses. We identified and characterized two previously unknown viruses, designated Baakal virus (BKAV) and Lakamha virus (LAKV). Sequencing and de novo assembly of the entire BKAV and LAKV genomes revealed that BKAV is an orthobunyavirus and LAKV is likely to belong to a new genus. LAKV was almost equidistant to the established peribunyavirus genera and branched as a deep rooting solitary lineage basal to herbeviruses. Virus isolation attempts of LAKV failed. BKAV is most closely related to the bird-associated orthobunyaviruses Koongol virus and Gamboa virus. BKAV was successfully isolated in mosquito cells but did not replicate in common mammalian cells from various species and organs. Also cells derived from chicken were not susceptible. Interestingly, BKAV can infect cells derived from a duck species that is endemic in the region where the BKAV-positive mosquito was collected. These results suggest a narrow host specificity and maintenance in a mosquito–bird transmission cycle.